2014
DOI: 10.1016/j.ygyno.2014.07.106
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in immune mediators associate with risk of cervical cancer

Abstract: Objective The immune system is critical for controlling the progression of HPV cervical disease and the development of cancer. This study aimed to identify cervical cancer susceptibility alleles in candidate immune-modulating genes. Methods Our family-based study involved a cohort of 641 probands (women with ICC / CIN III) and their biologic parents or siblings (641 trios). In the discovery phase (stage 1), involving 288 of the trios, 81 tag single nucleotide polymorphisms (SNPs) in 11 immune-modulating gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…Out of 350 HPV 16‐positive ICC patients with a fully sequenced E6 locus, we observed 130 patients with zero nonsynonymous E6 variants, 103 patients with one nonsynonymous E6 variant, 43 patients with two nonsynonymous E6 variants, and 74 patients with three or more nonsynonymous E6 variants. Participants with phylogenetically related HPV types were grouped according to our previous work as HPV 16‐related or HPV 18‐related strains and by variant A7 or A9 clades …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 350 HPV 16‐positive ICC patients with a fully sequenced E6 locus, we observed 130 patients with zero nonsynonymous E6 variants, 103 patients with one nonsynonymous E6 variant, 43 patients with two nonsynonymous E6 variants, and 74 patients with three or more nonsynonymous E6 variants. Participants with phylogenetically related HPV types were grouped according to our previous work as HPV 16‐related or HPV 18‐related strains and by variant A7 or A9 clades …”
Section: Methodsmentioning
confidence: 99%
“…High‐risk HPV clades have been identified as alpha‐9 (A9; comprised of HPV 16, 31, 33, 35, 52, 58, and 67) and alpha‐7 (A7; comprised of HPV 18, 39, 45, 59, 68, 70, 85, and 97) . We previously demonstrated that the most common high‐risk HPV types can also be defined as HPV 16‐related (HPV 16, 31, and 52) or HPV 18‐related (HPV 18 and 45) . Furthermore, HPV 16 can be classified into four major lineages (A, B, C, D) and several alphanumerical sublineages based on the broader genetic profile of the viral genome …”
Section: Introductionmentioning
confidence: 99%
“…This is the first study reporting the association between this polymorphism and NPC, since the majority of studies were performed with gastric and cervical carcinomas (Canedo et al, 2008;Zhang et al, 2014). Despite we have not found statistically significant differences, there might be a 30% increased risk in -56T carriers for the development of NPC or UNPC, which should be further analysed.…”
Section: −56c > T Ifngr1mentioning
confidence: 56%
“…Prolonged infection has been linked with a higher risk of developing HPV‐associated malignant processes, suggesting that immune‐mediated clearance of HPV infection underlies, at least in part, the development of HPV malignancies. Supporting this are findings from multiple studies linking polymorphisms in immune mediators to an increased risk of cervical cancer . For HPV‐associated oropharyngeal cancer, polymorphisms in immune mediators, such as transforming growth factor‐beta1 and tumor necrosis factor‐alpha, as well as pathways critical to genome integrity and programmed cell death, such as p53 and p73, are linked to an increased risk of oropharyngeal cancer …”
Section: Discussionmentioning
confidence: 86%
“…Supporting this are findings from multiple studies linking polymorphisms in immune mediators to an increased risk of cervical cancer. [14][15][16][17][18][19] For HPV-associated oropharyngeal cancer, polymorphisms in immune mediators, such as transforming growth factor-beta1 and tumor necrosis factoralpha, as well as pathways critical to genome integrity and programmed cell death, such as p53 and p73, are linked to an increased risk of oropharyngeal cancer. [20][21][22][23][24][25][26] Given elevated rates of both oropharyngeal as well as cervical cancer in relatives of patients with oropharyngeal SCC, education regarding the relationship between HPV and cancer should be offered to the patient and extended to their family members.…”
Section: Discussionmentioning
confidence: 99%